2008
DOI: 10.2215/cjn.04431007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Laboratory Evaluation of the Syndrome of Inappropriate Secretion of Antidiuretic Hormone

Abstract: Hyponatremia secondary to the syndrome of inappropriate secretion of antidiuretic hormone (SIADH) is a frequent cause of hypotonicity. Although the differential diagnosis with other causes of hypotonicity such as salt depletion is sometimes challenging, some simple and readily available biologic parameters can be helpful in the diagnosis of SIADH. In SIADH, urea is typically low; this is less specific for elderly patients, for whom lower clearance of urea accounts for higher values. Low levels of uric acid are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 61 publications
(58 reference statements)
3
97
1
7
Order By: Relevance
“…Several studies have used test infusions of isotonic saline to discriminate between these alternatives, but because our study was retrospective, we were unable to use this test. 11,20 Some studies have reported that, in patients in a state of volume depletion, volume repletion removes the stimulus for antidiuretic hormone release, allowing excess water to be excreted in a dilute urine and the serum sodium concentration to return toward normal. 21,22 According to this theory, instead of using an isotonic test infusion, we added in our study a criterion of volume depletion in which patients with a sustained increase in serum sodium concentration of !5 mEq/L and a sustained decrease in blood urea nitrogen, even with administration of hypotonic solution, were classified as volume depleted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used test infusions of isotonic saline to discriminate between these alternatives, but because our study was retrospective, we were unable to use this test. 11,20 Some studies have reported that, in patients in a state of volume depletion, volume repletion removes the stimulus for antidiuretic hormone release, allowing excess water to be excreted in a dilute urine and the serum sodium concentration to return toward normal. 21,22 According to this theory, instead of using an isotonic test infusion, we added in our study a criterion of volume depletion in which patients with a sustained increase in serum sodium concentration of !5 mEq/L and a sustained decrease in blood urea nitrogen, even with administration of hypotonic solution, were classified as volume depleted.…”
Section: Discussionmentioning
confidence: 99%
“…Those variables with P < 0.2 in the univariate analyses were included in the multivariate 9 Hannon and Thompson, 12 and Decaux and Musch. 20 analyses. The Hosmer-Lemeshow test was used to assess the goodness-of-fit for multivariate logistic regression models.…”
Section: Methodsmentioning
confidence: 99%
“…Graph demonstrating serum sodium concentrations in mmol/L and urine osmolalities in mosm/kg during infusion of 0.9% saline at 50 ml/h over 36 h. Note dilution of urine at 24 h of the study and prompt correction of hyponatremia 36 h after initiation of saline therapy. mmol/L if sodium intake is low (23). Uosm is always increased above plasma osmolality, although 2 L of isotonic saline infused at 16 ml/min has been shown to dilute the urine to 151 mosm/kg by unknown mechanisms (24).…”
Section: Discussionmentioning
confidence: 99%
“…A key means of distinguishing SIAD from other causes of hyponatremia has been the use of serum and urine biochemistries. SIAD is usually associated with an elevated spot urine sodium (> 20 mEq/L), elevated fractional excretion of sodium (> 0.55%), low blood urea nitrogen (BUN) and plasma uric acid, and low plasma renin activity and aldosterone, whereas the converse of these biochemistries is noted in hypo-and hypervolemic causes of hyponatremia [5].…”
Section: Syndrome Of Inappropriate Antidiuresismentioning
confidence: 99%